2021
DOI: 10.48129/kjs.splcov.15451
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of Antiviral Medicinal Compounds Against Sars Cov-2 Proteases

Abstract: The world is under siege from a global pandemic caused by a novel class of coronaviruses called severe acute respiratory syndrome coronavirus-2 (SARS CoV-2). These viruses cause severe respiratory illness leading to death. Molecular studies reveal that SARS CoV-2 proteases are involved in the processing of viral polyproteins. This study was conducted to obtain antiviral agents for SARS CoV-2 proteases. An extensive library of antiviral medicinal compounds was scrutinized to determine the probable interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It is established in the recent literature that a ligand bonded to the active site residues via a hydrogen bond brings functional changes in the protein structure resulting in the inhibition of protein function. [17][18] Therefore, these compounds could be involved in alleviating pain response in different types of disease which might have a promising role in alleviating chronic pain in TMD. These four compounds reduce the expression of CXC10, CXCR6 and IL1R1 and SDC4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is established in the recent literature that a ligand bonded to the active site residues via a hydrogen bond brings functional changes in the protein structure resulting in the inhibition of protein function. [17][18] Therefore, these compounds could be involved in alleviating pain response in different types of disease which might have a promising role in alleviating chronic pain in TMD. These four compounds reduce the expression of CXC10, CXCR6 and IL1R1 and SDC4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The sinomenium acutum root was the original source of an alkaloid called sinomenine, a chemical that can exhibit numerous pharmacological potentials including anti-angiogenic, anti-rheumatic, and immunomodulatory actions [ 17 ]. Recent in vitro and in vivo clinical trials have shown numerous biological potentials of this alkaloid (sinomenine), including antioxidant [ 18 ], anti-microbial [ 19 ], anti-inflammation [ 20 ], anticancer [ 21 ], antiviral [ 22 ], antidiabetic [ 23 ], anti-hypertensive [ 24 ], and anti-nociceptive (analgesia) actions [ 25 ]. Sinomenine has shown effective therapeutic actions against cardiovascular disease in rats [ 26 ].…”
Section: Introductionmentioning
confidence: 99%